2020
DOI: 10.3390/biom10081153
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae: A Promising Source of Valuable Bioproducts

Abstract: Microalgae are a group of autotrophic microorganisms that live in marine, freshwater and soil ecosystems and produce organic substances in the process of photosynthesis. Due to their high metabolic flexibility, adaptation to various cultivation conditions as well as the possibility of rapid growth, the number of studies on their use as a source of biologically valuable products is growing rapidly. Currently, integrated technologies for the cultivation of microalgae aiming to isolate various biologically active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 207 publications
(90 citation statements)
references
References 108 publications
(120 reference statements)
2
66
0
Order By: Relevance
“…It has been reported that some microalgae contain soluble proteins in their cytoplasm [ 3 , 4 ]. In addition, microalgae with chloroplasts contain soluble protein, central pyrenoid, and phytobiliproteins, although some microalgae, such as Arthrospira platensis , instead, have thylakoid sacs surrounding the peripheral cytoplasm associated with phycobilisomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some microalgae contain soluble proteins in their cytoplasm [ 3 , 4 ]. In addition, microalgae with chloroplasts contain soluble protein, central pyrenoid, and phytobiliproteins, although some microalgae, such as Arthrospira platensis , instead, have thylakoid sacs surrounding the peripheral cytoplasm associated with phycobilisomes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein is another important product of microalgae used as food/feed supplements. The protein content of microalgae varies from 30 to70% of dry weight depending on the species of microalgae as well as the culture conditions (Ejike et al 2017 ; Dolganyuk et al 2020 ). The concentration of nitrogen in the nutrient medium is known to affect protein accumulation in microalgae species.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the sequences of the 16S rRNA and 18S rRNA genes ( Appendix A , Appendix B and Appendix C ) made it possible to conclude that they fully corresponded to the genotypes of the microalgae Chlorella vulgaris , Arthrospira platensis , and Dunaliella salina . Since they are typical microalgae of the Baltic Sea and water bodies of the Kaliningrad region (Russia), their lipid potential was studied as a possible raw material basis for feed and dietary supplements [ 3 ].…”
Section: Resultsmentioning
confidence: 99%
“…Microalgae cultivation is attracting more research due to its ability to synthesize various biologically active substances, the rapid growth of biomass, and the possibility of adjusting their biochemical composition depending on the cultivation conditions [ 1 , 2 , 3 ]. Unlike heterotrophic microorganisms, which require various organic compounds for growth, single-celled photosynthetic organisms produce biomass from fully oxidized inorganic substances and mineral elements due to light energy converted during photosynthesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%